Срочноооооооооооооооооо

0 голосов
21 просмотров

Срочноооооооооооооооооо


image

Математика (79 баллов) | 21 просмотров
Дано ответов: 2
0 голосов

Решите задачу:



( \frac{x}{36} + \frac{12}{36}) - \frac{3}{36} = \frac{16}{36}
( \frac{x}{36} + \frac{1}{3}) - \frac{3}{36} = \frac{4}{9}
\frac{x}{36} + \frac{1}{3} - \frac{3}{36} = \frac{4}{9}
\frac{x}{36} + \frac{1}{4} = \frac{4}{9}
x + 9 = 16
x = 16 - 9
x = 7
(901 баллов)
0 голосов

Ответ:    х=7

Пошаговое объяснение:

(х/36 +12/36) - 3/36=16/36  

(х/36 +12/36) =16/36   +3/36

(х/36 +12/36) = 19/36  

х/36  = 19/36  - 12/36

х /36=  7/36

х=7

(86.0k баллов)